Bridging the skill gap through internships: Stakeholders theory perspective - Belinda, R. (Productivity)
The skill gap among the youth of today is widening and is resulting in unemployability. It is time to revisit the education system and work strategies to develop employability skills among students. One such strategy can be incorporating internships in the curriculum at the undergraduate and postgraduate levels across disciplines. While offering an internship course, it is of utmost importance that the stakeholders involved, namely the primary stakeholders, which include the interning student, the Higher Educational Institution (HEI) and the organisation in which the intern is placed, should maintain continuous communication through which all three of them benefit. This paper attempts to examine the perception of the stakeholders about bridging the skill gap through internships, and their advantages and challenges.- Reproduced
Keywords: Skill gap, Internships, Stakeholders theory perspective